Endovascular repair of abdominal aortic aneurysm-related type II endoleak: a multicenter study on the possibility of further intervention - Erdemutu, E.; Zhou, Chongbin; Ma, Ming; Hu, Liqiang; Wu, Jisiguleng; Dai, Xiangchen; Gao, Zhanfeng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundWe aimed to analyze the risk factors associated with Type II endoleak (T2EL) requiring reintervention after endovascular aneurysm repair (EVAR) for multicenter abdominal aortic aneurysms.MethodsA retrospective analysis was conducted on data from 614 patients with abdominal aortic aneurysms who underwent elective EVAR at three centers (Tianjin Medical University General Hospital, Affiliated Hospital of Inner Mongolia Medical University, Shanxi Provincial People's Hospital) from January 2017 to December 2021. After applying exclusion criteria, 375 patients were included in the study, with 50 patients in the T2EL-related reintervention group and 325 patients in the non-T2EL group. Single-factor and multiple-factor logistic analyses were used to identify high-risk factors, and ROC curve analysis was performed to determine the risk thresholds for mesenteric artery diameter, number of lumbar arteries, maximum aneurysm diameter, and proportion of intraluminal thrombus volume.ResultsThe rate of T2EL-related reintervention among the 375 patients was 13.33% (50/375). Single-factor analysis indicated that age, hypertension, maximum aneurysm diameter, proportion of intraluminal thrombus, diameter of inferior mesenteric artery (IMA), and number of patent lumbar arteries (LA) were risk factors for T2EL-related reintervention. Multiple-factor logistic analysis identified maximum aneurysm diameter, proportion of thrombus, IMA diameter, and number of patent LA as the main influencing factors for T2EL-related reintervention after EVAR. Significant risk factors for reintervention were maximum aneurysm diameter (OR = 1.043, 95% CI 1.015–1.072, P = 0.002), IMA diameter (OR = 3.901, 95% CI 1.116–13.632, P = 0.033), and number of LA (OR = 2.584, 95% CI 1.722–3.769, P < 0.001). A significant protective factor for reintervention was thrombus proportion (OR = 0.895, 95% CI 0.864–0.927, P < 0.001). ROC curve analysis showed that the risk thresholds for reintervention were an IMA diameter of 2.95 mm, intraluminal thrombus volume proportion <42.5%, number of LA ≤5.5, and aneurysm diameter of 53.55 mm.ConclusionCases with identified risk factors are considered to have a higher risk of T2EL-related reintervention after EVAR. Exceeding the new risk thresholds may indicate a higher likelihood of T2EL-related reintervention after EVAR.